K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

2 tháng 3 2017

\(x^2-x=0\)

\(\Leftrightarrow x\left(x-1\right)=0\)

\(\Leftrightarrow\left\{{}\begin{matrix}x=0\\x-1=0\end{matrix}\right.\Leftrightarrow\left\{{}\begin{matrix}x=0\\x=1\end{matrix}\right.\)

áp dụng định lí bezout :

thay x=0 vào \(f\left(0\right)=\left(0+1-1\right)^{10}+\left(0-0+1\right)^{10}=2\)

thay x=1 vào \(f\left(1\right)=\left(1+1-1\right)^{10}+\left(1-1+1\right)^{10}=2\)

\(\Rightarrow f\left(0\right)=f\left(1\right)\)

\(\Rightarrow\)so du la 2

Bài 1: 

a: \(5x^3-x^2-5x+1\)

\(=x^2\left(5x-1\right)-\left(5x-1\right)\)

\(=\left(5x-1\right)\left(x-1\right)\left(x+1\right)\)

b: \(x^2+4xy+4y^2-9\)

\(=\left(x+2y\right)^2-9\)

\(=\left(x+2y+3\right)\left(x+2y-3\right)\)

c: \(x^2-5x+6=\left(x-2\right)\left(x-3\right)\)